Comparison of Cycloplegic Refraction Versus Dynamic Retinoscopy in Children from 5 to 12 Years of Age : Comparison of Cycloplegic Refraction Versus Dynamic Retinoscopy - Shahid, Sharmeen; Maimoona Rehmat; Amna Mahmood; Farooq, Erum; Shanza Dastgir (Pakistan Journal of Health Sciences, 2022)
Refractive errors are a noteworthy cause of visual disruption worldwide. Objective: To compare the results of dynamic and cycloplegic retinoscopy in children. Methods: A descriptive-type cross-sectional study was conducted at the university of Lahore teaching hospital on 50 patients from 5 to 12 years of age. Approval was taken from the ethical board of the institution and informed consent from patient’s parents. Patients who had any other ocular pathology other than refractive errors were excluded. To study the refraction results in children, first in a dark room, retinoscopy without cycloplegic was performed then 1% cyclopentolate eye drops were used. After that retinoscopy was done under cycloplegic effect results were compared after being converted into spherical equivalent. Paired sample t-test was applied to compare means. P < .05 was taken as significant. Results: There were 25 males and 25 females. The mean age in years was 7.66 ±there were 12 myopic patients, 22 hypermetropic and 16 astigmatic patients. The mean logMar of visual acuity uncorrected was 0.5 ± 0.23 and the best corrected visual acuity was 0.1± 0.01. The mean S.E of right eye dynamic retinoscopy was 1.78±2.60, cycloplegic retinoscopy 1.52± 2.54 and of left eye was 1.72±49 and1.47± 2.34 respectively. It can be deduced that on average 0.26D more by dynamic retinoscopy. A significant correlation with r 0.96 and r 0.94 in left eye existed. Conclusion: There is a significant difference between cycloplegic retinoscopy and near retinoscopy. It was deduced that near retinoscopy showed more hypermetropic readings than cycloplegic retinoscopy